2008
DOI: 10.1007/s10800-008-9606-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergism in copper corrosion inhibition by sodium dodecylbenzenesulphonate and 2-mercaptobenzoimidazole

Abstract: The inhibition effects of sodium dodecylbenzenesulphonate (SDBS) and 2-mercaptobenzoimidazole (2-MBI) on the corrosion of copper in sulphuric acid solution have been studied using electrochemical impedance spectroscopy (EIS) and Tafel polarisation measurements. For 2-MBI, a monotonic increase in inhibition efficiency is observed as a function of concentration. Upon mixing 2-MBI and SDBS, concentration regions showing synergistic inhibition behaviour are identified and it is concluded that electrostatic interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…It is effective in basic and near‐neutral , but much less so in acidic solutions Another azole derivative, 2‐mercaptobenzimidazole (2‐MBI), offers higher corrosion protection in acidic environments. 2‐MBI, through its S atom in the mercapto group, is adsorbed strongly to Cu, presumably forming a thick, strongly adsorbed film on the surface .…”
Section: Introductionmentioning
confidence: 99%
“…It is effective in basic and near‐neutral , but much less so in acidic solutions Another azole derivative, 2‐mercaptobenzimidazole (2‐MBI), offers higher corrosion protection in acidic environments. 2‐MBI, through its S atom in the mercapto group, is adsorbed strongly to Cu, presumably forming a thick, strongly adsorbed film on the surface .…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases-the condensation product of an amine and ketone or aldehyde with general formula of R2C=NR are well-known organic inhibitors [20,21]. Some research work revealed that the inhibition efficiency of Schiff bases is much greater than that of corresponding amines and aldehydes and attributed this to the presence of an -HC=N-group in the molecules [22].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the bond between the adsorbed inhibitor molecules and the metal surface can be studied by the adsorption isotherms. Some authors have found that the adsorption of 2‐MBI molecules on steel and copper alloys obeys a Langmuir adsorption isotherm 12, 13, 16, 20. However, other bibliographic references report that this behavior has not been observed on Zn and steel surfaces 10, 15.…”
Section: Resultsmentioning
confidence: 99%
“…Organic compounds containing sulfur have been found to be good corrosion inhibitors in CO 2 ‐containing environments 9. It has been demonstrated that the heterocyclic compound, 2‐mercaptobenzimidazole (2‐MBI), is a good corrosion inhibitor for carbon steel 10–14, zinc 15, copper 16, and copper alloys 17, in acid environments (HCl, H 2 SO 4 , and H 3 PO 4 ). Figure 1 shows the chemical structure of 2‐MBI.…”
Section: Introductionmentioning
confidence: 99%